Culture, mind, and the brain current evidence and future directions. [article]. - Kitayana, Shinobu
Current research on culture focuses on independence and interdependence and documents numerous East-West psychological differences, with an increasing emphasis placed on cognitive mediating mechanisms. Lost in this literature is a time-honored idea of culture as a collective process composed of cross-generationally transmitted values and associated behavioral patters.-(from the author)
Keywords: Uskul, Ayse K; Neuro-culture interaction; Cultural values and practices; Independence/interdependence.; Individualism/Collectivism.; Neuro-plasticity.; Gene-culture reaction